Analisis Guru dalam Penerapan Kurikulum Merdeka di Sekolah Indonesia Kuala Lumpur (SIKL) - Dwi, Dara Fitrah; Sujarwo, Sujarwo; Friska, Novita; Haliza, Nurul; Amelia, Listri (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study is to find out and examine the "Analysis of the Implementation of the Independent Curriculum at the Indonesian School in Kuala Lumpur. This study was conducted using a phenomenological approach. This type of research is a qualitative study that looks and listens more closely and in detail to individual explanations and understandings of their experiences. The phenomenological approach is based on the researcher's interest in studying more deeply the phenomena experienced by key informants. The research was conducted at the Indonesian School in Kuala Lumpur. The informants in this study were teachers, school curriculum representatives, and school public relations. Data collection was carried out using several techniques, namely; (a) observation; (b) interviews; and (c) documentation studies. To ensure the validity of the data, several efforts were made as follows: (a) extending the data collection period, (b) conducting continuous and serious observations, (c) conducting triangulation, and (d) involving colleagues for discussion. From the results of the study in this study, it was found that there was an independent curriculum that was used as a reference in the driving school, which produced students who were noble, independent, critically reasoned, creative, had mutual cooperation, and a sense of diversity. The principal encouraged various participatory, unique, and innovative programs. Fostering cooperation with teachers who support their leaders to participate in realizing the vision and mission of the Indonesian school in Kuala Lumpur.